The Unofficial Guide to Microsoft Office Word 2007 - J.Clark David (Wiley, 2006)
Microsoft Office Word 2007 may be the top word processor, but to use it with confidence, you'll need to know its quirks and shortcuts. Find out what the manual doesn't always tell you in this insider's guide to using Word in the real world. How do you use the new Ribbon? What's the best way to add pictures? From deciphering fonts to doing mass mailings, first get the official way, then the best way from an expert.